2006
DOI: 10.1016/j.jvs.2006.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Flow reduction in high-flow arteriovenous access using intraoperative flow monitoring

Abstract: Flow reduction using intraoperative access flow monitoring is an effective and durable technique allowing for the correction of distal ischemia and cardiac insufficiency in patients with a high-flow autogenous access. The desired postoperative access flow of 400 mL/min is not associated with an increased risk of thrombosis. Flow reduction of prosthetic access is as effective; however, a higher access flow than the desired 600 mL/min seems to be necessary to achieve an acceptable patency in prosthetic accesses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
95
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(97 citation statements)
references
References 23 publications
0
95
0
2
Order By: Relevance
“…9 Another approach is to monitor the flow reduction in the venous limb of the fistula to prevent severe flow reductions that would promote fistula thrombosis. 24 In a series of 78 patients with ischemic steal syndrome and high fistula flow, banding was tailored to reduce fistula flow to 400 ml/min in autogenous grafts, and 600 ml/min in prosthetic grafts. Ischemic symptoms were relieved in 86% of patients with 91% of autogenous fistulae remaining patent at 12 months.…”
Section: Fistula Bandingmentioning
confidence: 99%
See 2 more Smart Citations
“…9 Another approach is to monitor the flow reduction in the venous limb of the fistula to prevent severe flow reductions that would promote fistula thrombosis. 24 In a series of 78 patients with ischemic steal syndrome and high fistula flow, banding was tailored to reduce fistula flow to 400 ml/min in autogenous grafts, and 600 ml/min in prosthetic grafts. Ischemic symptoms were relieved in 86% of patients with 91% of autogenous fistulae remaining patent at 12 months.…”
Section: Fistula Bandingmentioning
confidence: 99%
“…Ischemic symptoms were relieved in 86% of patients with 91% of autogenous fistulae remaining patent at 12 months. 24 Graft survival with banding was less successful with prosthetic grafts (only 58% patent at 1 year) and the authors suggested that higher flow rates (> 750 ml/min) in the graft were required to prevent thrombosis. 24 More recently, the minimally invasive limited ligation endoluminal-assisted revision (MILLER) technique describes a modified method of banding.…”
Section: Fistula Bandingmentioning
confidence: 99%
See 1 more Smart Citation
“…PTFE strip was placed around narrowed segment to prevent vein dilatation and flow increase. 5 Other technique was T-banding, that avoids anastomotic aneurisms. 15 Revision using distal inflow (RUDI) was another procedure used for treatment of high-flow AVF.…”
Section: Discussionmentioning
confidence: 99%
“…3 It was postulated to reduce access blood flow if exceeded 2 L/min or cardiac index was higher than 3.0 L/min/m 2 , and after solving anemia, over hydration and hypertension. 3,4 Among various options for vascular access flow restriction, [3][4][5][6][7][8] there are methods allowing for standardized inflow decrease. 9,10 The aim of the study is to present the utility of external dilator-assisted banding (EDAB) with no endovascular catheterization.…”
Section: Introductionmentioning
confidence: 99%